Invisible Gender Inequality in Rural China: Exploring the Reasons for Son Preference and Daughter Preference (Global Journal of Human-Social Science, 2022)
Son preference seems to be disappearing in the current discursive environment, replaced by the emergence of daughter preference in social communication. Different from previous studies of son preference in China that focus on quantitative data, this paper is based on an ethnographic study of a remote rural village in Shanxi Province, China. Through the use of participant observation, focus groups, and semi-structured interviews, the paper concludes that patriarchal systems persist, and son preference develops dynamically. Among others, the author concludes that (1) the patriarchal system is a necessary foundation for the existence of son preference, (2) the concealment of son preference is an aftereffect of gender reproductive selection and a major variable of marital stress, and (3) daughter preference is a variant of traditional gender expectations.
Keywords: son preference; patriarchal system; gender reproductive selection; marital stress; gender expectations